2014
DOI: 10.1021/om501004d
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Room-Temperature Activation of Csp3–Cl Bonds by Cheap and Air-Stable Nickel(II) Complexes of (N-Thioether) DPPA-Type Ligands

Abstract: Reaction of the diphosphine (P,P) ligand N­(PPh2)2(n-PrSMe) (1) or N­(PPh2)2(p-(SMe)­C6H4) (2) with [Ni­(NCMe)6]­[BF4]2 in a 2:1 molar ratio afforded the bis-chelated, dicationic Ni­(II) complexes [Ni­(1)2]­[BF4]2 (3) and [Ni­(2)2]­[BF4]2 (4), respectively. Both complexes were characterized in solution by various spectroscopic techniques and in the solid state by X-ray diffraction studies. In the presence of Zn metal used as cheap reductant, complexes 3 and 4 activate the inert C–Cl bonds of dichloromethane at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Very recently, our group also reported a series of bis-chelate dicationic group 10 metal complexes of ligands 192 and 196 (Scheme ). While the Pd­(II) derivatives 206 and 207 were used as linkers between Janus Au-coated silica microspheres to allow a simple and visual assessment of the anchoring of S-functionalized compounds on metal surfaces (see section ), the Ni­(II) species 208 and 209 were found to undergo CH 2 Cl 2 activation in the presence of Zn(0) as reducing agent under mild conditions . The 31 P NMR spectra of the resulting complexes 210 and 211 clearly showed the dissymetrization of the PNP ligands with retention of one P­(III) and formation of one P­(V) center (phosphonium ylide); this ligand class is outside the scope of this review and will therefore not be detailed.…”
Section: Sulfur-based Functionalizationsmentioning
confidence: 99%
“…Very recently, our group also reported a series of bis-chelate dicationic group 10 metal complexes of ligands 192 and 196 (Scheme ). While the Pd­(II) derivatives 206 and 207 were used as linkers between Janus Au-coated silica microspheres to allow a simple and visual assessment of the anchoring of S-functionalized compounds on metal surfaces (see section ), the Ni­(II) species 208 and 209 were found to undergo CH 2 Cl 2 activation in the presence of Zn(0) as reducing agent under mild conditions . The 31 P NMR spectra of the resulting complexes 210 and 211 clearly showed the dissymetrization of the PNP ligands with retention of one P­(III) and formation of one P­(V) center (phosphonium ylide); this ligand class is outside the scope of this review and will therefore not be detailed.…”
Section: Sulfur-based Functionalizationsmentioning
confidence: 99%
“…9 Very recently, a combination of dicationic Ni(II) complexes, in which the metal center is bis-chelated by two N-thioether-functionalized DPPA-type ligands, and Zn metal was found to readily perform the activation of C sp3 −Cl bonds under mild conditions and afford mixed phosphinephosphonium ylide species. 10 Since iron is an earth-abundant, cheap, and nontoxic metal, 11 its coordination complexes have recently attracted increasing attention as alternatives to precious metal complexes in homogeneous catalysis. 12 Among the various catalytic applications of iron complexes, we note the catalytic oligomerization of ethylene 13,14 and the atom-transfer or organometallicmediated radical polymerization (ATRP and OMRP, respectively).…”
Section: ■ Introductionmentioning
confidence: 99%
“…that (i) bis-chelated dicationic Pd(II) complexes with ligands 1 and 2 could be used to assess molecular anchoring on Au(111) surfaces (Janus microspheres), 4 (ii) the N-functionalization influences the behavior of Ni(II) complexes containing such tritopic P,P,S ligands in catalytic ethylene oligomerization, 6a and (iii) that a combination of dicationic Ni(II) complexes containing two chelating ligands 1 or 2, and Zn metal allows the activation of both C sp3 −Cl bonds of CH 2 Cl 2 under mild conditions and affords mixed phosphine, phosphonium ylide species. 10 Further indications that subtle changes in ligand design can strongly affect the nature of the resulting coordination complexes were also provided by the reactions between FeCl 2 and ligand 1 or 2 (1:1 molar ratio) since they led, under strictly similar reaction conditions, to an infinite coordination polymer or a dinuclear complex, respectively. 11 It was concluded that electronic factors accounted for the unusual unsymmetrical chelation of the iron center (Chart ligand/metal molar ratio used in the synthesis is retained in the structure of the complex, as confirmed by the elemental analysis on ground and dried crystals (see Experimental Section).…”
Section: Introductionmentioning
confidence: 97%
“…The study of the electronic structure of first-row transition metal ions in relation with their stereochemistry is a very relevant field in coordination and biological chemistry, and it is essential to analyze how stereochemistry, electronic structure, and magnetic properties correlate. , We became interested in the coordination chemistry of N -thioether-functionalized DPPA-type ligands, such as (Ph 2 P) 2 N­(CH 2 ) 3 SMe ( 1 ) and (Ph 2 P) 2 N­( p -C 6 H 4 )­SMe ( 2 ), with an alkyl or an aryl spacer, respectively (Chart , top) because of (i) the versatility of the thioether function, which can act as an intra- or intermolecular donor toward a metal center or be used to deposit/anchor complexes on metal surfaces, and (ii) the possibility to evaluate the differences of reactivity induced by a change of the linker that connects the PNP moiety and the thioether donor group, for example, when going from a flexible propyl to a rigid phenyl. Previous studies have shown that (i) bis-chelated dicationic Pd­(II) complexes with ligands 1 and 2 could be used to assess molecular anchoring on Au surfaces (Janus microspheres), (ii) the N -functionalization influences the behavior of Ni­(II) complexes containing such tritopic P , P , S ligands in catalytic ethylene oligomerization, and (iii) a combination of dicationic Ni­(II) complexes containing two chelating ligands 1 or 2 and Zn metal allows the activation of both C sp3 –Cl bonds of CH 2 Cl 2 under mild conditions and affords mixed phosphine, phosphonium ylide species …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation